2014
DOI: 10.1089/ten.tea.2013.0749
|View full text |Cite
|
Sign up to set email alerts
|

Link N and Mesenchymal Stem Cells Can Induce Regeneration of the Early Degenerate Intervertebral Disc

Abstract: Link N is a naturally occurring peptide that can stimulate proteoglycan synthesis in intervertebral disc (IVD) cells. IVD repair can also potentially be enhanced by mesenchymal stem cell (MSC) supplementation to maximize extracellular matrix (ECM) production. In a previous study, we have shown that Link N can inhibit osteogenesis and increase the chondrogenesis of MSCs in vitro. The aim of the present study was to determine the potential of MSCs and Link N alone or in combination with regard to tissue repair i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 49 publications
3
56
2
Order By: Relevance
“…(2014) [80] could show successful MSC survival without any pre-conditioning with growth factors if injected into bovine coccygeal organ culture model along with the short peptide link-N. They injected only about 10 5 cells into the bovine disc and found a high cell viability after 21 days of organ culture.…”
Section: Organ Culture Biomaterials and Stem Cell Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…(2014) [80] could show successful MSC survival without any pre-conditioning with growth factors if injected into bovine coccygeal organ culture model along with the short peptide link-N. They injected only about 10 5 cells into the bovine disc and found a high cell viability after 21 days of organ culture.…”
Section: Organ Culture Biomaterials and Stem Cell Therapymentioning
confidence: 99%
“…During recent years the application of various hydrogels for NP and AF repair has been widely followed-up [80,82-85]. One approach is the injection of fibrin-genipin adhesive hydrogel to seal large AF defects [86,87].…”
Section: Organ Culture Biomaterials and Stem Cell Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Cryptic peptides [64] which recruit resident progenitor cells to sites of tissue damage to effect ECM/remodelling to promote repair processes have been described [65] and of relevance to repair of the degenerate IVD. Link-N, a cryptic fragment of linkprotein has been applied to a number of IVD studies and shown to stimulate the resident IVD cell populations as well as progenitor stem cells to upregulate production of collagen and aggrecan and stimulate repair of the degenerate IVD [66][67][68][69][70][71][72]. Future studies will hopefully uncover basic data applicable to the application of the resident progenitor stem cell population we have observed as a therapeutic cell type.…”
Section: Spine Research Issn 2471-8173mentioning
confidence: 99%
“…Moreover, MSCs induce nucleous pulposus cells to suppress MMPs and inflammatory cytokine production in vitro (94). MSCs when administered together with Link-N can restore GAGs content and increase the expression of collagen type II in bovine mild degenerated discs (95). In clinical studies, injection of autologous bone marrow MSCs into nucleous pulposus improved pain and disability and water content was increased; albeit, disc height was not restored at 12-months postinjection (96).…”
Section: Cell Replacementmentioning
confidence: 99%